Modeling the Impact of Shadow Financial Transactions on the Country's Financial Potential - Inna Tiutiunyk; Iryna Kozhushko (Financial Markets, Institutions and Risks)
The article summarizes the arguments and counterarguments within the scientific debate on the issue of raising the level of the country's financial potential. The main goal of the conducted research is to model the impact of shadow operations on the level of the country's financial potential. Analysis of the dynamics of publication activity on issues of the shadow economy and financial potential in publications indexed by the Scopus and Web of Science databases, bibliometric analysis of the connection between the concept of the shadow economy and other economic categories made it possible to identify theories that are most closely related to this concept: theory innovative management, theory of liberalization, theory of political economy, institutional theory. The urgency of solving this scientific problem lies in the fact that in the conditions of a protracted economic crisis and active military operations on the territory of Ukraine, significant volumes of shadow operations negatively affect the attractiveness of the country from the side of international partners, the level of its financial stability, the ability to withstand economic and political risks. Methods of dynamic analysis, Erlang's formula, methods of regression analysis became the methodical toolkit of the conducted research, the period of the study was 2008-2021. The article presents the results of an empirical analysis of the financial potential of Ukraine, which showed a gradual increase in its level until 2021. At the same time, the forecast values of the level of financial potential in 2022 indicate its significant reduction and the need to implement a set of measures aimed at maintaining the macroeconomic stability of the country and its financial independence. The study empirically confirms and theoretically proves that the main drivers of the shadowing of the economy include: a low level of material or criminal responsibility for these actions, an excessive level of tax burden, the inability of the government to monitor the compliance of economic entities with existing norms and laws in the country. The results of the conducted research can be useful for public administration bodies in the context of improving the policy of countering shadowing of the economy as a component of increasing the country's financial potential.